الإجهاد النفسي لدى الطالب العامل بجامعة الوادي - بنين, امال; بنين, ابتسام (جامعة الوادي - University of Eloued, 2016)
هدفت هذه الدراسة إلى التعرف على مستويات الإجهاد النفسي لدى عينة من الطلبة العمال بجامعة الوادي في ضوء متغيرات العمر والجنس والحالة العائلية. وباتباع المنهج الوصفي بشقيه الاستكشافي والفارقي وتطبيق مقياس الإجهاد النفسي واستخدام كل من التكرارات النسب المئوية، واختبار "ت" تم التوصل إلى النتائج التالية: - نسبة 30.90% من مجموع أفراد العينة تعاني من إجهاد نفسي مرتفع مقابل نسبة 69.09% لذوي الإجهاد النفسي المنخفض. - لا توجد فروق ذات دلالة إحصائية بين أفراد العينة في الإجهاد النفسي تبعا لمتغيري الفئة العمرية والحالة العائلية في حين توجد فروق ذات دلالة إحصائية بينهم تبعا لمتغير الجنس لصالح الإناث. وقد نوقشت نتائج هذه الدراسة في ضوء الإطار النظري والدراسات السابقة مع اقتراح بعض التوصيات المتعلقة بالموضوع. This study aimed to identify psychological stress levels among a sample of working student in El˗oued University in light of variables : age, sex and marital status. Using the descriptive-comparative method, the implementation of psychological stress scale and using frequencies ,percentages and " T "test, the study resulted in the following: -30.90 % of the sample suffer from a high psychological stress, compared to 69.09% of them suffer from a low psychological stress. -There were no differences with statistical significance between the sample members in the psychological stress according to age and the marital status, while there were differences with statistical significance between them according to sex in favour of females . The study results were discussed in the light of theoretical frame work and the previous studies suggesting some recommendations related to the study topic.
دراسة استكشافية في ضوء بعض المتغيرات الديمغرافية
مقال
Keywords: الصحة النفسية – الإجهاد النفسي – الطالب العامل; mental health - psychological stress -working student